Does maturity signals high risk and high return? - Budiarso, Novi Swandari; Pontoh, Winston (Indonesia Accounting Journal, 2019)
The objective of this study is to examine the interaction between firm maturity and firm growth opportunities over risk and its impact on returns. This study uses 135 firms listed in Indonesia Stock Exchange during 2010 to 2016 as sample which gives 945 as total observed data. This study conducts path analysis in term for hypothesis testing and finds that firm maturity has significant role to increase the risk which gives impact on increasing the returns. In context of Indonesian firms, the findings imply that mature firms will have higher risk and higher returns.